2020
DOI: 10.1002/art.41165
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Assessment Strategies and Disease Subsets in Giant Cell Arteritis: Data From an International Observational Cohort

Abstract: Objective Diagnostic assessment in giant cell arteritis (GCA) is rapidly changing as vascular imaging becomes more available. This study was undertaken to determine if clinical GCA subsets have distinct profiles or reflect differential diagnostic assessments. Methods Patients were recruited from an international cohort and divided into 4 subsets based on a temporal artery (TA) abnormality (positive TA biopsy [TAB] or halo sign on TA ultrasound [TA‐US]) and/or evidence of large vessel (LV) involvement on imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
(26 reference statements)
4
21
0
1
Order By: Relevance
“…Furthermore, the patient’s perspective of the disease can also act as a bias in this group of patients when often non-classical or unrelated headache and visual disturbance are symptoms commonly over-reported. Finally, the younger age observed in this cohort (mean ± SD 69.4 ± 7.9 years) and high prevalence of constitutional symptoms (86.5% of the cohort) favour the extra-cranial variant, as observed in other studies [ 3 , 4 , 6 ].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Furthermore, the patient’s perspective of the disease can also act as a bias in this group of patients when often non-classical or unrelated headache and visual disturbance are symptoms commonly over-reported. Finally, the younger age observed in this cohort (mean ± SD 69.4 ± 7.9 years) and high prevalence of constitutional symptoms (86.5% of the cohort) favour the extra-cranial variant, as observed in other studies [ 3 , 4 , 6 ].…”
supporting
confidence: 85%
“…Gribbons et al [ 3 ] recently published an analysis of the Diagnostic and Classification Criteria for Vasculitis (DCVAS) data and showed that patients exclusively with large vessel involvement (TA-negative and evidence of large vessel involvement on imaging) differed considerably from patients with isolated temporal artery involvement (TA-positive and evidence of large vessel involvement on imaging) in terms of both their clinical profiles and their demographic characteristics. In parallel, several studies have shown that the expression of specific cytokines and chemokines, at a vascular (tissue) or extravascular level (serum or plasma), are associated with differential risks of cranial ischaemia, indicating that there is an immunological predilection towards the observed clinical phenotype [ 4 ].…”
mentioning
confidence: 99%
“…Features of GCA often vary from patient to patient and depend in part on which arteries are predominantly affected. 18 In fact, cohort studies have identified two main groups of patients: cranial GCA (C-GCA), the classical and most common phenotype; and largevessel GCA (LV-GCA), which was identified more recently and is considered less common. 19 The described patterns of C-GCA and LV-GCA are not mutually exclusive and overlapping clinical phenotypes are common.…”
Section: Discussionmentioning
confidence: 99%
“…Gribbons et al sought to identify subsets of GCA, and showed that GCA with LVLs was divisible into two groups based on the involvement of temporal artery (37). TCZ improved clinical outcomes not only in GCA patients with cranial lesions but also in patients who presented with LVLs and PMR without cranial lesions (38).…”
Section: Discussionmentioning
confidence: 99%